Molecular and serological detection of Leptospira and Ricktettsia in patients with acute febrile illness - Daisy Vanitha John (Universiti Malaysia Sabah, 2014)
Leptospirosis is a zoonotic disease which is caused by the spirochete, Leptospira interrogans (L interrogans). Rodents generally serve as the main carrier for Leptospirosis and transmit the disease to humans through cuts and abrasions in the skin or through mucous membranes of the eyes, nose or throat. High seroprevalence was recorded in Sabah, among people living within the national park is likely due to high exposure and contact with wild animals. Diagnosis of Leptospirosis is challenging due to a wide diversity of clinical symptoms which mimic regular symptoms of fever. Lipl32 is a major outer membrane protein, which is present only in pathogenic strains of Leptospira. Studies show that ELISA is able to detect Leptospira-specific antibodies earlier than the gold standard method, the Microscopic Agglutination Test (MAT). In this study, we have used codon optimized synthetic gene encoding Lipl32 and transfected into E coli expression vector BL21 (DE3). The recombinant Lipl32 protein was expressed after induction with IPTG which resulted in approximately a 40kDa protein. The purified recombinant Lipl32 protein was used as an antigen for detecting Leptospira-specific antibody by ELISA. Preliminary_ results showed that the recombinant Lipl32 antigen was able to detect Leptospiraspecific IgM and IgG in human serum samples. Hence, this method could be used for diagnostic purposes and in epidemiological investigations of Leptospirosis.